Investigating the Effect of Self-Regulated Strategy Development on Tertiary EFL Students' Writing Skills - Kasyfur Rahman; Imansyah Imansyah; I Made Permadi Utama (Universitas Islam Negeri (UIN) Mataram, 2019)
This study aimed to investigate the relative effect of Self-Regulated Strategy Development (SRSD) teaching approach on tertiary EFL students’ writing. During two months, sixty EFL University students enrolling in basic writing course took part in this project and were divided into experimental and control groups. Pre- and post-tests were carried out to garner the intended data pertinent to the students’ writing scores. A mixed-design ANOVA was carried out to analyze the changes of writing scores of the respective groups since the assumption of homogeneity of regression slopes for the planned Analysis of Covariance was not met. The statistical evidence showed that there was a significant difference between the two groups in terms of writing scores at the significant value sig .00 < .05. The data also suggested that students who were taught using SRSD relatively outperformed their counterparts in the control group. The empirical evidence demonstrates that the use of SRSD as an instructional approach to some extent positively affects EFL students’ writing skill.